LAW ON THE PROTECTION OF CHILDREN FROM DOMESTIC VIOLENCE ACCORDING TO LAW NO. 23 OF 2004 - Dany Try Hutama Hutabarat; Evi Yulyantika; Hikma Rotun; Dewi Syamsiah; Laila Siti Nurhaliza; Khairunnisa Nasution; Ade Hastina Putri; Sri Indah Lestari; Nurainul Mardiah; Mimi Arimbi; Ahmad Fajar Mukti (Transpublika Publisher, 2022)
The violence in the family is frequently difficult to detect, and the public paradigm continues to assume that something happens in the family is private. The presence of Laws number 23 of 2004 on the elimination of domestic violence is expected to protect state citizens from unsettling senses and forms of violence, but the number of incidents of domestic violence in everyday life instantly increases. As the Writer will examine the function of Laws number 23 of 2004 prohibiting domestic violence in providing protections for state citizens, particularly those who are victims of domestic abuse. By focusing on the following questions: Is it sufficient to safeguard state citizens who are victims of domestic violence? and What should be done to reduce the number of domestic violence cases in Indonesia? The conclusion drawn by the author is that Laws number 23 of 2004 prohibiting domestic violence have been sufficient to protect victims and offer an elementary level of protection to law enforcement. However, its implementation must be coherent and systematic, not only with the country according to its instruments of power, but also with the population that supports the eradication of domestic violence.